Penguatan Karakter Percaya Diri dan Sikap Kritis Anak melalui Keteladanan Guru Pendidikan Agama Islam - Wahyuni, Endang Sri; Suyudi, M.; Masduki, Moh. (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Issues of low self-confidence and weak critical thinking skills—such as fear of asking questions, hesitation to share opinions, and difficulty analyzing information—are still common among students. These problems can hinder learning and personal development. Teacher role modeling is considered an effective approach to strengthen these characters, especially in Islamic Religious Education (PAI), where character formation aligns with Islamic values. This study aims to examine: (1) the development of self-confidence and critical thinking at SDN 2 Karanggebang; (2) the forms of teacher role modeling in PAI classes; and (3) supporting and inhibiting factors in its implementation.This qualitative descriptive research collected data through interviews, observations, and documentation, then analyzed them inductively to identify patterns and draw conclusions.Findings show that self-confidence at the school is developed in three aspects: behavioral, emotional, and spiritual. Critical thinking is strengthened through students’ ability to give simple explanations, build basic reasoning skills, and draw conclusions. Teacher role modeling appears in three forms: qudwah al-‘ibadah, which fosters spiritual confidence and basic critical explanation; qudwah al-karimah, which shapes behavioral confidence and deeper critical thinking; and qudwah syaja’ah, which builds emotional confidence. Supporting factors include teacher consistency, a positive school environment, and support from parents and the community. Inhibiting factors include limited personal interaction time, a content-heavy curriculum, and the long process needed to shape character.